In-school marketing in South African primary schools: An exploratory study - S. Cassim; K. McIntosh (South African Journal of Business Management, 2011)
In-school marketing is a global phenomenon that has recently become the focus of much debate and criticism. Concerns about the potentially negative impact marketing practices may have on school going children have been raised across the globe. In response a variety of policies have been developed in different countries to regulate the practice of in-school marketing. This paper explores commercial activities in South African primary schools through an empirical study of primary school principals. The study investigates the policies and procedures in place to guide the practice of marketing in schools and the views of principals on Issues pertaining to in-school commercialism. The findings of this paper indicated an absence of formal policies to guide the practice of commercial activities in primary schools. Principals however supported the need for policies on in-school commercialism to protect children. They also expressed the view that commercial activities can only be tolerated when they offer added value to the school.
Keywords: 650